Perspectives on the changing healthcare system: teaching systems-based practice to medical residents - Martinez, Johanna (Co-Action Publishing, 2013)
PURPOSE: The Accreditation Council for Graduate Medical Education restructured its accreditation system to be based on educational outcomes in six core competencies. Systems-based practice is one of the six core competencies. The purpose of this report is to describe Weill Cornell Medical College's Internal Medicine Residency program curriculum for systems-based practice (SBP) and its evaluation process. METHODS: To examine potential outcomes of the POCHS curriculum, an evaluation was conducted, examining participants': (1) knowledge gain; (2) course ratings; and (3) qualitative feedback. RESULTS: On average, there was a 19 percentage point increase in knowledge test scores for all three cohorts. The course was rated overall highly, receiving an average of 4.6 on a 1–5 scale. Lastly, the qualitative comments supported that the material is needed and valued. CONCLUSION: The course, entitled Perspectives on the Changing Healthcare System (POCHS) and its evaluation process support that systems-based practice is crucial to residency education. The course is designed not only to educate residents about the current health care system but also to enable them to think critically about the risk and benefits of the changes. POCHS provides a framework for teaching and assessing this competency and can serve as a template for other residency programs looking to create or restructure their SBP curriculum.